Gelasia attariana (Scorzonerinae, Cichorieae, Asteraceae), a new species from NW of Iran, inferred from morphological and molecular data - Ebrahimi, Atefeh; Hatami, Elham; Safavi, Seyed Reza; Mirtadzadini, Mansour (Phytotaxa, 2023)
Gelasia attariana is described as a new species from northwest of Iran, near the border to Azerbaijan. The new species is morphologically similar to G. cinerea and G. wendelboi, mainly because of sharing caulescent perennial life form, entire lanceolate leaves with 3–7 parallel veins, tomentose indumentum of phyllaries and glabrous achenes without carpopodium, but differs in plant height, indumentum type of stems and leaves, length/width ratio of leaves, leaves color, apex of leaves and length of achenes and pappus. Morphological comparisons and taxonomic relationships of G. attariana with its closely related taxa are discussed. Consistent with morphological data, molecular evidences based on nrDNA ITS sequences confirmed that the new species can be recognized as a distinct taxon from its close relatives. Description, images of living plants and distribution map of the new species are also provided.